(untitled) (Anwer Khan Modern Medical College Journal, 2013)
Legal term hurt means bodily pain, injury or wound and disease or infirmity caused to any person. Abrasion, bruise, laceration, fracture, dislocation, incised wound, stab wound, puncture, penetrating wound, firearm wound, bomb blast wound, burn, scald are common types of injury or hurt. Different types of weapons or means used to cause hurts are blunt, sharp and pointed weapons, firearms, bombs, heat, electricity and corrosives. For legal purposes, hurts are grouped as grievous hurt and simple hurt. There are eight categories of grievous hurt. In reporting hurt cases, the clinical state of the victim with full description of the wounds are noted and an opinion regarding their legal state i.e. whether grievous or simple, age of the injury, type of the weapon or means causing the injury, whether inflicted by others or self inflicted etc. is given. These help the court to give its judgment. There are enacted laws describing section, numbers, types of crime and their punishments. Anwer Khan Modern Medical College Journal Vol. 4, No. 2: July 2013, Pages 37-41 DOI: http://dx.doi.org/10.3329/akmmcj.v4i2.16941